Rhythm in the First Movement of Bartók’s Contrasts: Performance and Analysis - Daphne Leong; Daniel Silver; Jennifer John (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2008)
This article examines rhythm in the first movement of Bartók's Contrasts to aid performance of the work, and to deepen analytical understanding of its structure and of Bartók’s rhythmic language.